6(z-2)+6z-4=

Simple and best practice solution for 6(z-2)+6z-4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(z-2)+6z-4= equation:


Simplifying
6(z + -2) + 6z + -4 = 0

Reorder the terms:
6(-2 + z) + 6z + -4 = 0
(-2 * 6 + z * 6) + 6z + -4 = 0
(-12 + 6z) + 6z + -4 = 0

Reorder the terms:
-12 + -4 + 6z + 6z = 0

Combine like terms: -12 + -4 = -16
-16 + 6z + 6z = 0

Combine like terms: 6z + 6z = 12z
-16 + 12z = 0

Solving
-16 + 12z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + 12z = 0 + 16

Combine like terms: -16 + 16 = 0
0 + 12z = 0 + 16
12z = 0 + 16

Combine like terms: 0 + 16 = 16
12z = 16

Divide each side by '12'.
z = 1.333333333

Simplifying
z = 1.333333333

See similar equations:

| -2x-50=0 | | 4r-7r+9r= | | -2x/7+9=435/49 | | -2x-50=-640 | | x=(49/12) | | 4(7x-5/6)=-514/3 | | 2/7(1/2+5x)=71/7 | | 5/8+2x/3=21/8 | | graphx=5 | | 2y-7+3y-7= | | -x/7+3/8=29/56 | | 2y-5+4y-9= | | y=-3.9x+2.8 | | 6x-5/5=-7 | | 9x/16=81 | | 3/5+x=3/5 | | 1/2-3x/5=-11/2 | | X-1/2=-13/2 | | Y+-14=9 | | 5/6t+2/3t=45 | | 5x-8/4=7 | | (15x^4y^5/18x^6y)/(25x^12y^4/12x^5y^4) | | -5x/7+9=33/7 | | 5/8+7x=117/8 | | -2(7x+4)= | | 15+6*7+x=88 | | B=9/8(j-65) | | 3h+5=50 | | 3/108 | | 8/9-5x/9=-37/9 | | 0.8d-17+d=2d-9-0.4d | | 3h+b=3 |

Equations solver categories